The use of rivaroxaban for short- and long-term treatment of venous thromboembolism - Cohen, Alexander T.; Dobromirski, Mark (Thrombosis and Haemostasis, 2012)
Venous thromboembolism (VTE) is a major healthcare concern and affects more than 1.6 million individuals each year worldwide. Long-term complications include recurrent VTE, chronic thromboembolic pulmonary hypertension and post-thrombotic syndrome. Rivaroxaban is an oral, direct factor Xa inhibitor that has advantages over traditional VTE therapies, including minimal drug and food interactions and no requirement for routine coagulation monitoring. It is currently approved for VTE prevention in adult patients undergoing elective hip or knee replacement surgery. This review evaluates the potential clinical implications of the multicentre, randomised EINSTEIN studies (EINSTEIN DVT and EINSTEIN EXT), which investigated rivaroxaban for the treatment and prevention of recurrent VTE. In EINSTEIN DVT, rivaroxaban was non-inferior to the standard of care (enoxaparin plus a vitamin K antagonist) for recurrent VTE in patients with acute deep-vein thrombosis (DVT) without pulmonary embolism (PE). In EINSTEIN EXT, extended-duration rivaroxaban had superior efficacy to placebo in patients with confirmed DVT or PE who had received 6–12 months of prior VTE treatment. Rivaroxaban was associated with an acceptable safety profile in both studies. The net clinical benefit (efficacy and safety end-points combined) of rivaroxaban was significantly greater than its comparators. The EINSTEIN studies are the first demonstration that a single drug - rivaroxaban - can be effective for both the initial treatment of DVT and prevention of recurrent VTE. Moreover, the simple, once-daily oral administration of rivaroxaban could potentially improve adherence to extended-duration VTE treatment compared with the current standard of care in individuals with confirmed DVT or PE.
Keywords: Anticoagulants; enoxaparin; rivaroxaban; treatment; venous thromboembolism